2021
DOI: 10.1002/ca.23743
|View full text |Cite
|
Sign up to set email alerts
|

Cyamella (a popliteal sesamoid bone) prevalence: A systematic review, meta‐analysis, and proposed classification system

Abstract: The cyamella is a rare, generally asymptomatic, knee sesamoid bone located in the proximal tendon of the popliteal muscle. Only two studies have investigated cyamella presence/absence in humans, putting ossified prevalence rates at 0.57%–1.8%. We aim to (a) determine cyamella prevalence in a Korean population, (b) examine coincident development of the cyamella and fabella, and (c) perform a systematic review and meta‐analysis on the cyamella in humans. Medical computed tomography scans of 106 individuals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 47 publications
(126 reference statements)
1
11
0
Order By: Relevance
“…In this article, we introduced the CATAM rubric and used it to critically appraise a recently published anatomical MA (Kacprzyk et al, 2020). There have been other anatomical MAs recently published (Aldabe et al, 2019; Bellier et al, 2020; Berthaume & Bull, 2021; Cheruiyot et al, 2021; Dreher et al, 2018; Graves et al, 2017; Harvie et al, 2019; Koziej et al, 2020; Morelli et al, 2019; Nallikuzhy et al, 2018; Roberts et al, 2021; Sirico et al, 2019; Solewski et al, 2021; Stefura et al, 2018; Tomaszewska et al, 2018; Tomaszewska et al, 2018; Tomaszewski et al, 2017; Tomaszewski et al, 2017; Vikse et al, 2016a, 2016b; Whitley et al, 2020; Yammine, 2013, 2014b, 2014c, 2014d; Yammine et al, 2015; Yurasakpong et al, 2021). We believe that the running paper that we used is an exemplary anatomical MA (Kacprzyk et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we introduced the CATAM rubric and used it to critically appraise a recently published anatomical MA (Kacprzyk et al, 2020). There have been other anatomical MAs recently published (Aldabe et al, 2019; Bellier et al, 2020; Berthaume & Bull, 2021; Cheruiyot et al, 2021; Dreher et al, 2018; Graves et al, 2017; Harvie et al, 2019; Koziej et al, 2020; Morelli et al, 2019; Nallikuzhy et al, 2018; Roberts et al, 2021; Sirico et al, 2019; Solewski et al, 2021; Stefura et al, 2018; Tomaszewska et al, 2018; Tomaszewska et al, 2018; Tomaszewski et al, 2017; Tomaszewski et al, 2017; Vikse et al, 2016a, 2016b; Whitley et al, 2020; Yammine, 2013, 2014b, 2014c, 2014d; Yammine et al, 2015; Yurasakpong et al, 2021). We believe that the running paper that we used is an exemplary anatomical MA (Kacprzyk et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Le Minor (1992) looked at the prevalence of the cyamella in 34 primate genera and reported that the cyamella does not appear in all nonhuman primate genera, but when it does, it has a half‐ellipsoid shape with one flat articular surface and a second rounded nonarticular surface. In humans, the occurrence of the cyamella is low, estimated at 1%–2% of individuals (Berthaume & Bull, 2021). Two studies looked at the cyamella in New Zealand white (NZW) rabbits ( Oryctolagus cuniculus ; Lagomorpha Crum et al, 2003; Orhan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the occurrence of the cyamella is low, estimated at 1%-2% of individuals (Berthaume & Bull, 2021). Two studies looked at the cyamella in New Zealand white (NZW) rabbits (Oryctolagus cuniculus; Lagomorpha Crum et al, 2003;Orhan et al, 2005).…”
mentioning
confidence: 99%
“…The cyamella, an ossified cartilaginous body within the proximal tendon or at the musculotendinous junction of the popliteal muscle, is a rarely observed and generally asymptomatic sesamoid bone of the knee. [1][2][3][4] The prevalence of ossified cyamella is reported to be between 0.57 and 1.8%. 3 A symptomatic cyamella is very rare and described in the literature only in few case reports.…”
mentioning
confidence: 99%
“…[1][2][3][4] The prevalence of ossified cyamella is reported to be between 0.57 and 1.8%. 3 A symptomatic cyamella is very rare and described in the literature only in few case reports. 2,4,5 The fabella is also a sesamoid bone typically found in the lateral head of the gastrocnemius.…”
mentioning
confidence: 99%